Analysis of cross-sectional layers of corrosion using metallographic microscope - Szala, Barbara; Greiner-Wrona, Elżbieta; Kwaśniak-Kominek, Monika (Geology, Geophysics and Environment, 2013)
The aim of this study was to identify and recognize the phenomena of corrosion between glass-metal connections. Experiments were carried out on historical and contemporary samples treated with corrosion catalysts and the results helped to identify the most corrosive conditions for historic objects. Microscopic observations were carried out on cross-sectional layers of specially prepared samples of enamel on copperplate, corresponding to the chemical composition of historic samples-enamel from Limoges. Subsequently, a series of techniques were implemented improving the quality of the image. A 20-micron thick corrosion layer can be observed and recorded using this method. Observations allowed to determine the quality and technology aspects of the enamel exposed to the processes. The diagnosis of corrosion processes is extremely important in order to determine the application technique of enamel on the metal substrate. Microscopic images therefore revealed the formation of corrosion products. This proved an efficient and effective way to provide information on the thickness, color and structure of the observed layers. Micro-photographs from a metallographic microscope allowed for further planning and the subsequent use of a Scanning Electron Microscope (SEM) with an Energy Dispersive Spectrometer (EDS) and Raman Spectrometer (RS) - mitigating the need for the analysis of the entire sample’s surface. Most corroded places have been identified and the metal proved to be more reactive material. The impact of factors such as: the technique of layering the enamel, structural inclusions, pitting corrosion, temperature and the environment’s impact have been clearly linked to the overlap of the corrosion processes.